Entomophthoromycosis and mucormycosis as causes of pneumonia in Vietnamese potbellied pigs. (January 2018) - Evans, Dawn E.; Kawabata, Atsushi; Wilson, Leslie D.; Kim, Kenneth; Dehghanpir, Shannon D.; Gaunt, Steve D.; Welborn, Matt; Grasperge, Britton; Gill, Marjorie S.
Two Vietnamese potbellied pigs ( Sus scrofa ) had respiratory disease and, on autopsy, both pigs had large masses in the lungs and thoracic cavity. Microscopically, pulmonary and pleural masses contained large areas with hyphae surrounded by hypereosinophilic cellular debris rimmed by abundant eosinophils, lymphocytes, plasma cells, and histiocytes with occasional multinucleate giant cells. The hypereosinophilic debris usually formed tight cuffs, or "sleeves" around the hyphae, compatible with Splendore-Hoeppli–like material. The fungal organisms were determined by PCR to be Conidiobolus incongruus in one pig and Mucor circinelloides in the other. Entomophthoromycosis and mucormycosis should be included in the differential diagnoses for swine pneumonia, particularly when there is evidence of granulomatous pulmonary masses and pleural effusion with eosinophilic inflammation.